The development of aggressive behaviour in middle childhood - ŽUKAUSKIENĖ, RITA (Psichologija, 1997)
Findings from several studies are suggesting that the most of the growth of aggression occurs in the very young age and in adolescence. However,it is very little known about the gender differences in the growth and decrease of aggressive behaviour in middle childhood. Besides, most studines concerning development of aggressive behaviour have been carried out in Western cultures. Understanding the development of aggressive behaviour in childhood and adolescence in such East-European country as Lithuania presents a significant scientific and practical interest. T his study assessed gender differences in the development of aggression in the middle childhood. Peer and child interview, teacher and parents ratings of behaviour problems, and sociometric status w ere obtained for 695 first-through-seventh grade children, both boys and girls. One year later parents of 220 students repeatedly completed CBCL 4/18 form. T he results indicate that the mean tevels of boys aggressive behaviour decreases gradually during the middle childhood, starting from 9-10-years of age. Girls showed a lower level of aggression compared w ith boys, and the difference in the decrease of aggression. Aggressive behaviour was related with peer rejection, especially for boys. Results are discussed in terms of future directions for longitudinal research on the gender differences in the development of aggression.
Keywords: aggressive behaviour; middle childhood; development; gender differences